Financial Programming and Policy the Case of Turkey. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The art of financial programming is a central element in the design of IMF-supported macroeconomic adjustment programs. This volume, edited by Richard Barth and William Hemphill, includes contributions from staff members of the IMF institute and introduces the reader to the concepts and tools of analysis needed to formulate a financial program. The book presents a series of workshops that explain the accounting identities, behavioral relationships, and forecasting techniques that underlie the constuction of a financial program. The workshops use the case of Turkey to illustrate the techniques, and the complete data set for Turkey is included on a diskette (supplied in a back-cover pocket).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet